Disease‐specific health‐related quality of life instruments for IgE‐mediated food allergy. Issue 7 (16th May 2014) - Salvilla, S. A.; Dubois, A. E. J.; Flokstra‐de Blok, B. M. J.; Panesar, S. S.; Worth, A.; Patel, S.; Muraro, A.; Halken, S.; Hoffmann‐Sommergruber, K.; DunnGalvin, A.; Hourihane, J. O'B.; Regent, L.; et al.
Abstract This is one of seven interlinked systematic reviews undertaken on behalf of the European Academy of Allergy and Clinical Immunology as part of their Guidelines for Food Allergy and Anaphylaxis, which focuses on instruments developed for IgE‐mediated food allergy. Disease‐specific questionnaires are significantly more sensitive than generic ones in measuring the response to interventions or future treatments, as well as estimating the general burden of food allergy. The aim of this systematic review was therefore to identify which disease‐specific, validated instruments can be employed to enable assessment of the impact of, and investigations and interventions for, IgE‐mediated food allergy on health‐related quality of life (HRQL). Using a sensitive search strategy, we searched seven electronic bibliographic databases to identify disease‐specific quality of life (QOL) tools relating to IgE‐mediated food allergy. From the 17 eligible studies, we identified seven disease‐specific HRQL instruments, which were then subjected to detailed quality appraisal. This revealed that these instruments have undergone formal development and validation processes, and have robust psychometric properties, and therefore provide a robust means of establishing the impact of food allergy on QOL. Suitable instruments are now available for use in children, adolescents, parents/caregivers, and adults. Further work must continue to develop a clinical minimal important difference for food allergy and for making these instruments available in a wider range of European languages.